Full‐scale shaking table test and numerical modeling of a 3000‐liter legged storage tank isolated with a vertical rocking isolation system - Reyes, Sergio I.; Almazán, José L.; Vassiliou, Michalis F.; Tapia, Nicolás F.; Colombo, José I.; de la Llera, Juan C. (Earthquake engineering & structural dynamics, 2022)
This paper presents the numerical and experimental evaluation of a vertical‐rocking isolation (VRI). This evaluation is done by 1‐D shaking table tests performed on a full‐scale legged storage tank of 3000‐liters capacity and its representation through a simple yet representative rigid lumped‐mass model approach. The isolation system setup consisted of four ISO3D‐2G devices, each one placed on each leg of the tank, which uses high‐damping natural rubber to generate the restoring and dissipative forces. The ISO3D‐2G device is vertically flexible and laterally rigid, enabling the isolation mechanism of the rocking motion of the tank. The experiments were carried out using three white noise for the system identification and 17 ground motions inputs for the system validation. The measured variables included the lateral acceleration and displacement of the tank, and the vertical and rotational behavior of the isolation interface. The identification results showed a vertical‐rotational coupled fundamental mode that is highly dependent on the amplitude of deformation, with a period varying from 0.5 to more than 1 s, depending on the intensity of the motion. The maximum displacement of the tank at the top remained below 13 cm with total accelerations of nearly 0.3 g, both for motions with Peak Ground Acceleration (PGA) values ranging from 0.3 to 0.8 g. The mean maximum values were predicted with the simplified model with errors of less than 10% and 21% for displacements and accelerations, respectively. Finally, the results show that the behavior of vertical‐rocking isolated structures can be predicted by simplified models with reasonable errors and that the development of simple design guidelines and equations for VRI systems is possible.